Al-Ḥīlah al-Shar'iyyah as a Method in Responding to Prayer Problems in Space - Siti Marhamah; Mahsun Mahsun (Al-Ahkam, 2021)
This paper describes the prayer problem for Muslim astronauts in space and provides solutions using the al-ḥīlah al-shar'iyyah method. This paper is qualitative with descriptive-analytic research methods with data sourced from the literature. This paper finds that with the al-ḥīlah al-shar'iyyah method, Muslim astronauts can still carry out their obligations as a mukallaf. They get rukhṣah (dispensation), both related to the direction of the qibla and the determination of prayer times. Rukhṣah, as a result of the al-ḥīlah al-shar'iyyah method, helps Muslim astronauts in two conditions at once, first, in their position as scientists who carry out scientific missions. Second, in his position as a Muslim with his obligations to carry out the sharī'ah.